Critical Social Work Education and Practice: An Investigation among Educators and practitioners in the Kurdistan Region - Salih, Asst.L.Sangar Y. Salih (Sulaimani Journal for Humanities, 2026)
This research aimed to investigate the extent to which critical perspective is applied in both social work education and practices in the Kurdistan region. Two primary questions guided this inquiry: firstly, to what extent is critical perspective applied in social work education? secondly, how do social work practitioners perceive their roles as change agents within their employing institutions? The study employed a mixed-methods approach, combining surveys and qualitative interviews as well as focus group discussions to gather comprehensive insights from 112 social work educators, students, and practitioners. The findings revealed that due to the stubborn rules and habits, changing how social work programs work in the region is quite difficult. The results also indicated that despite efforts to diversify teaching and evaluation methods, traditional techniques are still applied, which are not supportive to develop critical thinking skills among students. Additionally, social work practitioners think critically, but they don't always act on those thoughts as their institution’s rules and habits make it hard for them to do so. The results show the need to revisit institutional policies and procedures to guarantee supportive institutional environments that empower social work educators and practitioners to not just think critically, but also put their critical thoughts into action. Future research should also delve deeper into the underlying factors contributing to the persistence of traditional teaching and evaluation methods within social work programs.
Keywords: Critical thinking; social work; Kurdistan region; critical practice